Preferência de Aphis craccivora, Koch por variedades locais de feijão-de-corda oriundas de Pentecoste, Ceará - Ferreira, Antonia Débora Camila de Lima (2015)
Currently the production of cowpea is taking ever greater proportions, and thereby arousing the interest of many producers for this culture. The attack of pests is among factors that affect production, being the black aphid considered key pest. The control of this pest can be accomplished through the use of resistant plants, resistance may occur in cultivars or in landraces. The objective of this study was to compare natural resistance of cowpea landraces genotypes against Aphis craccivora as well as the effects caused in its biology. In the first trial a free choice test was done using 21 genotypes compared to four standards. In this trial sowings were performed in 300 mL polystyrene cups arranged in a randomized block design consisting of 6 replicates and 25 treatments. It was found that the analyzed genotypes presented genetic variability in relation to against A. craccivora, resistance, and formed seven groups: Highly resistant (BRS Guariba, TVU 408 P2, Enrica pobre, Das Almas, CE-13 Selection and Ritinha), Resistant (CE-55, 40 dias 1, Praiano), Intermediate (Seridó, Sel. CE-42, 7 semanas), susceptible (Vinagre 1, Pitiúba, Rabo de calango Fígado de galinha, BR 17-Gurgueia) and highly susceptible (Roxão 1 (CE-13), Cabecinha, Isabel 1, VITA-7, Rita Joana, Milagroso, Bengala). After screening of these genotypes, six were selected to compose the second trial, which corresponded to the determination of biological parameters, four resistants: Ritinha, Enrica Pobre, Das Almas e Sel. CE-13, and two susceptible: Roxão 1(CE-13) e VITA-7. This test consisted of six treatments and six replications arranged in a randomized blocks at a greenhouse. Daily observations were made to determine the biological parameters: time of one generation, generation mortality, overall fertility, reproductive period, post-reproductive period and period of a cycle. From these dada, the population parameters were calculated: Intrinsic rate of increase (rm) and the finite rate of increase (λ). The different genotypes influence the biology A. craccivora. VITA-7 and Roxão1 (CE-13) were more suitable for the development of aphid providing superior fertility, greater reproductive period and longevity of adults. Genotypes Das Almas and Ritinha provided deleterious effects in individuals, causing 100% morality, being antibiose the main resistance mechanism.